АРАБ ТИЛИ ҲАҚҚЫНДА УЛЫЎМА МАҒЛЫЎМАТ - Ишаев, Ж. (SCIENCE and SOCIETY, 2019)
There is given some interesting information about the Arabian language, possibilities to learn this language in our country, history of development the language and pecularities of this language.
Keywords: grammar; dictionary; alphabet; letter; madrasah; country; literal; dialect; Arabian